Pengaruh Pemberian Mikoriza pada Pertumbuhan Bibit Tanaman Karet dalam Root Trainer - Putra, Riko Cahya; Hidayati, Umi (Jurnal Agro Industri Perkebunan, 2025)
Roots are organs in rubber plants that play a role in absorbing nutrients, including from inorganic fertilization. The application of mycorrhiza can increase the role of rubber plant roots in nutrient absorption. This research aims to determine the application of mycorrhiza to increase the growth of rubber plants in root trainer nurseries. The research was carried out from April to September 2022 at the Bogor-Getas Research Unit experimental field, Salatiga. The experimental design used a completely randomized design consisting of 8 treatments and eight replications. The treatments in this study were control without fertilization, root fertilizer every 2 weeks, mycorrhiza (5 and 10 g/plant), and a combination of mycorrhiza (5 and 10 g/plant) with root fertilizer (every 2 and 4 weeks). The mycorrhiza treatment (5 and 10 g/plant) with root fertilizer every 2 and 4 weeks showed growth in plant height, stem diameter, root weight, and plant weight, which was not significantly different compared to root fertilizer every 2 weeks. Higher relative agronomic effectiveness compared to root fertilizer every 2 weeks as standard treatment was obtained in mycorrhiza treatments (5 and 10 g/plant) with root fertilizer every 2 weeks (RAE 106% and 135%). These results show that mycorrhiza can increase plant growth and relative agronomic effectiveness without reducing liquid inorganic fertilizer applied through the roots